Development of Bedaquiline-Loaded SNEDDS Using Quality by Design (QbD) Approach to Improve Biopharmaceutical Attributes for the Management of Multidrug-Resistant Tuberculosis (MDR-TB) - Rao Nargis Jahan; Zafar Khan; Md. Sayeed Akhtar; Mohd Danish Ansari; Pavitra Solanki; Farhan J. Ahmad; Mohd Aqil; Yasmin Sultana (MDPI AG, 2023)
Background: The ever-growing emergence of antibiotic resistance associated with tuberculosis (TB) has become a global challenge. In 2012, the USFDA gave expedited approval to bedaquiline (BDQ) as a new treatment for drug-resistant TB in adults when no other viable options are available. BDQ is a diarylquinoline derivative and exhibits targeted action on mycobacterium tuberculosis, but due to poor solubility, the desired therapeutic action is not achieved. Objective: To develop a QbD-based self-nanoemulsifying drug delivery system of bedaquiline using various oils, surfactants, and co-surfactants. Methods: The quality target product profile (QTPP) and critical quality attributes (CQAs) were identified with a patient-centric approach, which facilitated the selection of critical material attributes (CMAs) during pre-formulation studies and initial risk assessment. Caprylic acid as a lipid, propylene glycol as a surfactant, and Transcutol-P as a co-surfactant were selected as CMAs for the formulation of bedaquiline fumarate SNEDDS. Pseudo-ternary phase diagrams were constructed to determine the optimal ratio of oil and Smix. To optimize the formulation, a Box-Benkhen design (BBD) was used. The optimized formulation (BDQ-F-SNEDSS) was further evaluated for parameters such as droplet size, polydispersity index (PDI), percentage transmittance, dilution studies, stability studies, and cell toxicity through the A549 cell. Results: Optimized BDQ-F-SNEDDS showed well-formed droplets of 98.88 ± 2.1 nm with a zeta potential of 21.16 mV. In vitro studies showed enhanced drug release with a high degree of stability at 25 ± 2 °C, 60 ± 5% and 40 ± 2 °C, 75 ± 5%. Furthermore, BDQ-F-SNEDDS showed promising cell viability in A549 cells, indicating BDQ-F-SNEDDS as a safer formulation for oral delivery. Conclusion: Finally, it was concluded that the utilization of a QbD approach in the development of BDQ-F-loaded SNEDDS offers a promising strategy to improve the biopharmaceutical properties of the drug, resulting in potential cost and time savings.